Edukasi dan Pembinaan Guna Meningkatkan Sektor Usaha Mikro, Kecil dan Menengah (UMKM) di Desa Dauh Puri Kauh - Ida Ayu Rosa Dewinta; I Putu Yudi Prabhadika; A.A. Ngurah Gede Punia Artawan P (Postgraduated Community Service Journal, 2024)
The community has an important role in obtaining education related to developing knowledge, one of which is knowledge of the quality of MSMEs (Micro, Small and Medium Enterprises). MSMEs have a very large role in Indonesia's economic development. As much as 60% of Indonesia's economic strength is in the MSME sector. However, many people still do not understand the importance of managing business permits, taxation and accounting records for MSMEs. Problems occur because MSME owners are very unfamiliar with the initial steps that must be taken in running a business, namely those related to digital marketing, processing business permits, taxation and accounting recording systems. Limitations that often occur are in adopting new technology and innovation in the production or marketing process as well as from a financial perspective, apart from that it is also related to tax issues, high tax burdens or lack of understanding regarding tax obligations can be a problem for MSMEs. The solution taken to overcome the lack of understanding related to digital marketing, business licensing, taxation and accounting information systems is providing education related to Business Licensing Applications, Taxation, Accounting Information Systems and Marketing Digitalization for the MSME sector. Assistance will be provided regarding the procedures for applying for Business Licensing, Digital Marketing, Taxation in accordance with the MSME business classification and the Accounting Information System related to MSME business financial records. Service providers provide sharing sessions for both academics, practitioners and MSMEs related to these topics.